Late Cardiac Rupture after Amplatzer Septal Occluder Implantation - Arnaz, Ahmet; Turkekul, Yasemin; Yalcinbas, Yusuf; Saygili, Arda; Sarioglu, Tayyar (TEXAS HEART INST, 2016)
Transcatheter device implantation has become an attractive alternative to surgery in the closure of atrial septal defects in selected patients. However, it can lead to early and late sequelae, some of them life threatening. For example, 79 days before her admission to our emergency department with sudden-onset respiratory distress and respiratory arrest (leading to cardiac tamponade and rupture), a 22-year-old woman had undergone percutaneous closure of an atrial septal defect. We describe the damage and its treatment. Although the adverse effects of transcatheter device implantation are rare, physicians should know that these events can be life threatening. Further data are needed to prevent such sequelae and to design new devices. It is of utmost importance that patients and their family members be informed both of possible sequelae and of life-saving interventions to be administered at early diagnosis.
Keywords: Balloon occlusion/adverse effects/instrumentation/standards; device removal; heart atria/injuries; heart septal defects; atrial/therapy; minimally invasive surgical procedures/adverse effects; prostheses and implants/adverse effects; septal occluder device/adverse effects; treatment outcome; wounds; penetrating/etiology